Identifikasi Pemahaman Guru Tentang Penggunaan Teknologi Informasi dan Komunikasi (TIK) Dalam Pembelajaran Matematika Di SMAN 1 Krueng Sabee - Anzora Anzora; Irma Aryani; Nurlaila Nurlaila; Ade Irfan (Jurnal Dedikasi Pendidikan, 2020)
Teacher’s understanding of the use of information and communication technology needs to be considering the current era globalization where education in technologycal development. The results of this study indicate that the teacher’s understanding of the types of ICT is good, this was obtained 87,5% of teacher’s expressed understanding. Teacher’s understanding of the fuctions of various types of ICT already understood this was pbtaind 62,5% of teacher’s expressed understanding. The teacher’s understanding of how to use ICT is classified as good, it was obtained 62,5% of teacher’s expressed understanding. Teacher understanding of the  way to deliver material using ICT is classified as good it is obtained 50% of teacher expressed understanding. Teacher’s undestanding of the steps of using ICT is sufficient, this was obtained by 50% of teacher’s saying they understood enough. The teacher’s understanding of the positive impact of using ICT is already good, it was obtained 62,5% of teachers expressed undestanding. Teacher’s understanding of the negative impact of using ICT is good, it was obtained 62,5% of teachers expressed understanding. Teacher’s understanding of the advantages of using ICT is classified as good, this was obtained 87,5% of teacher’s expressed very understanding. Teacher’s understanding of the weaknesses of using ICT is classified as good, of teachers expresed understanding. While the teacher’s understanding of the procedures for delivering material using ICTs has not been classified as good..